1995
DOI: 10.1093/oxfordjournals.jhered.a111578
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Analysis of Paternity and Reproduction in Arctic Grizzly Bears

Abstract: We report data from analyses of microsatellite loci of 30 grizzly bear family groups which demonstrate that each cub in a litter can be sired independently, and we derive estimates of maximum reproductive success for males, from an Arctic population in northwestern Alaska that is minimally affected by human activities. These analyses were made possible by the use of single-locus primers that amplified both of an individual's alleles at eight microsatellite loci and by detailed knowledge of maternal/offspring r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(69 citation statements)
references
References 0 publications
4
62
0
2
Order By: Relevance
“…Our paternity analyses indicated that one of five litters (20%) that were completely censused in Big Bend NP (BIBE20-21) contained half-sibs sired by resident males. Multiple paternity in mammals is not unusual and has been noted in brown (Ursus arctos L., 1758) and black bears (Craighead et al 1995;Schenk and Kovacs 1995), whitetailed deer (Odocoileus virginianus Zimmermann, 1780) (DeYoung et al 2002), and pronghorn (Antilocapra americana Ord, 1815) (Carling et al 2003). On the other hand, quantification of the prevalence of this behavior in the family Ursidae has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our paternity analyses indicated that one of five litters (20%) that were completely censused in Big Bend NP (BIBE20-21) contained half-sibs sired by resident males. Multiple paternity in mammals is not unusual and has been noted in brown (Ursus arctos L., 1758) and black bears (Craighead et al 1995;Schenk and Kovacs 1995), whitetailed deer (Odocoileus virginianus Zimmermann, 1780) (DeYoung et al 2002), and pronghorn (Antilocapra americana Ord, 1815) (Carling et al 2003). On the other hand, quantification of the prevalence of this behavior in the family Ursidae has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Assessments of sociological characteristics of nongregarious species of carnivores that have utilized both field and molecular data are less common (Craighead et al 1995;Lunn et al 2000). Nevertheless, such studies can be instrumental in the conservation of rare and threatened species because knowledge of dispersal patterns, relatedness groupings, and kinship is instrumental in recovery plans.…”
Section: Introductionmentioning
confidence: 99%
“…Males are able to devote their reproductive effort directly toward acquiring multiple females because they are not required for successful rearing of young (Trivers 1972), nor do they have to invest effort in courting females prior to copulation. In some polygynous species where males defend females, females are known to behave promiscuously, that is, they mate with males other than the ones defending or guarding them (Gibbs et al 1990;Pemberton et al 1992;Amos et al 1993;Westneat 1993;Morin et al 1994;Craighead et al 1995;Gray 1997a, b). What underlies (e.g.…”
Section: Ca)mentioning
confidence: 99%
“…From a biological perspective, molecular genetic analyses have been utilized to uncover important characteristics of natural populations such patterns of gene flow , reproductive success (Craighead et al 1995), genetic diversity (Paetkau and Strobeck 1994;Paetkau et al 1995;Waits et al 1998a), and evolutionary history (Taberlet and Bouvet 1994;Waits et al 1998b;Wooding and Ward in press;Talbot and Shields in press a). From a forensic standpoint, researchers have demonstrated the ability to use genetic information to differentiate species (Cronin et al 1991a;Waits and Ward in press), to trace individuals within a species to a particular geographic area (Waits 1996), and to identify individuals within a population (Paetkau and Strobeck 1994;Paetkau et al 1995).…”
Section: Overviewmentioning
confidence: 99%